Hepatitis E Virus Shows More Genomic Alterations in Cell Culture than In Vivo - Sari, Gulce (Pathogens, 2019)
Hepatitis E Virus (HEV) mutations following ribavirin treatment have been associated with treatment non-response and viral persistence, but spontaneous occurring genomic variations have been less well characterized. We here set out to study the HEV genome composition in 2 patient sample types and 2 infection models. Near full HEV genome Sanger sequences of serum- and feces-derived HEV from two chronic HEV genotype 3 (gt3) patients were obtained. In addition, viruses were sequenced after in vitro or in vivo expansion on A549 cells or a humanized mouse model, respectively. We show that HEV acquired 19 nucleotide mutations, of which 7 nonsynonymous amino acids changes located in Open Reading Frame 1 (ORF1), ORF2, and ORF3 coding regions, after prolonged in vitro culture. In vivo passage resulted in selection of 8 nucleotide mutations with 2 altered amino acids in the X domain and Poly-proline region of ORF1. Intra-patient comparison of feces- and serum-derived HEV gt3 of two patients showed 7 and 2 nucleotide mutations with 2 and 0 amino acid changes, respectively. Overall, the number of genomic alterations was up to 1.25× per 1000 nucleotides or amino acids in in vivo samples, and up to 2.84× after in vitro expansion of the same clinical HEV strain. In vitro replication of a clinical HEV strain is therefore associated with more mutations, compared to the minor HEV genomic alterations seen after passage of the same strain in an immune deficient humanized mouse; as well as in feces and blood of 2 immunosuppressed chronically infected HEV patients. These data suggest that HEV infected humanized mice more closely reflect the HEV biology seen in solid organ transplant recipients.